Upaya Meningkatkan Prestasi Belajar Al Qur’an Hadits Melalui Pembelajaran Baca Tulis Qur’an (BTQ) MI Miftahul Huda Jatisari Kecamatan Kepung Kabupaten Kediri - Mega Dwi Susanti (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The Qur'an Hadith is part of the subject of Islamic religious education given to understand and practice the Qur'an so that it is able to read eloquently, translate, conclude the content of the content, copy and memorize selected verses and understand and practice selected hadiths as a deepening and expansion of the study of the study of the Qur'an Hadith from Madrasah Ibtidaiyah and as a provision to follow the next level of education, however, in learning, there must be obstacles and obstacles in learning, therefore researchers carry out BTQ learning assistance which aims to find out the supporting and inhibiting factors of efforts to improve the achievement of the Qur'an Hadith through learning BTQ (Read Write the Qur'an), then to help improve the achievement of learning the Qur'an Hadith and to find out the results or responses of students to the achievements of class V students at MI Miftahul Huda. From the results of research, learning to read and write the Qur'an can help students in learning islamic religious education subjects, especially in the subjects of the Qur'an Hadith.